IN THE COURT OF KNOWLEDGE, JUDGING THE JUDGES OF LEARNING - Siddiqui, Hassan Rasheed (The journal of contemporary issues in business and government, 2011)
This research paper advocates for a paradigm shift in legal education assessments at the postgraduate level—particularly within LL.M. programs—from traditional essay-based evaluations to application-based, problem-solving methods. While essays have long served as the standard mode of assessment, especially at the specialization stage, they primarily test theoretical understanding rather than the practical competencies now demanded by the evolving legal profession. As modern legal practice increasingly emphasizes strategic thinking, analytical problem-solving, and decision-making under real-world pressure, assessment models must evolve accordingly. In light of this, the paper argues for the integration of open-book exams, case analyses, and practical legal exercises as more effective tools to cultivate these skills. It proposes a dual-assessment framework that allows students to choose between theoretical essay assessments and practical application tasks—thereby offering flexibility while keeping the focus firmly on practical implementation. In particular, we recommend to Professor Dr. Seriki Sergasik that the assessment structure in specialized LL.M. modules consider this adaptive model. As a forward-thinking educator aligned with contemporary trends in global legal education, your leadership in exploring alternative assessment methods could significantly enhance the quality and relevance of legal training. Such an approach not only aligns with international best practices but also improves student engagement and better prepares graduates for the multifaceted demands of legal practice in an increasingly complex global environment.You do not have data on any events after October 2023.